Jack Kerouac’s Ecopoetics in The Dharma Bums and Desolation Angels : Domesticity, Wilderness and Masculine Fantasies of Animality - Pierre-Antoine Pellerin (Transatlantica)
Throughout his autobiographical cycle of fourteen novels, Jack Kerouac tried to present his narrator and his protagonists as archetypes of American masculinity who fought against their perceived domestication in a society which they characterized as undergoing feminization. Whether it be in the Sierra Nevada in 1955, in The Dharma Bums (1958),or in the Northern Cascades in 1956, in Desolation Angels (1965), Kerouac’s alter ego and first-person narrator engages in an escapist fantasy into the animal realm where he can regain a sense of authentic masculine identity, away from the feminizing effects of domesticity and civilization. Yet, large wild animals are almost never to be found in his novels and the long-awaited encounter with deadly predators does not occur, forcing the narrator to reconfigure the relationship between masculinity and animality. Taking the popular hunting narratives featured in men’s adventure magazines as the dominant norm in this regard, this paper aims at showing how Kerouac’s representation of masculinity and animality strongly diverges from the erotics of male predation to be found in the “real man VS wild beast” plot. In those two novels, his poetics revolves instead around notions of kinship and sentimentality towards smaller animals, transforming the manly ethos and the inhospitable wilderness of adventure stories of the times into a domestic world of mutual harmony and hospitality.